DESAIN PROTOTIPE PADA STARTUP TALENTKU MENGGUNAKAN METODE LEAN UX STARTUP - Arlisa Kumala Rofik; Tri Sagirani; Sri Hariani Eko Wulandari (Jurnal Teknologi dan Terapan Bisnis, 2020)
Talentku is a market validation survey based on the user need to connect the students who have talent and want to hone their talents with companies/organizations that need talent for external and internal activities. The company needs a User Interface (UI) and User Experiences (UX) design as a base building platform. Strategies needed to design the UI/UX to run efective and efficient by prioritizing Just in Time Production. So the problem is how to design the UI/UX of my talent platform effectively and efficiently. The solution used to solve the above problem is designing User Interfaces and User Experiences using Lean UX Startup method. This method is pros "faster, smarter UX, research and learning". Results derived from this research is a prototype final that is a combination of prototype A and B that are validated in terms of criticism and suggestion through the questionnaire. The result of prototype A was selected for 13 featured, and prototype B was selected for 2 featured. Color scheme matching hexa #FE706E, as a branding form in the application Talentku and the font is Segoe UI.